Aspekte der »Mystik« in China - Reiter, Florian C. (Zeitschrift für Religionswissenschaft, 1996)
This contribution focuses on the comparability of basically Christian concepts of religious mysticism and Taoist religion. The article therefore takes a short sketch of essential features of medieval Christian mystics as a clear-cut starting point. Is religious Taoism a mystic religion? This question occurs when we read in some German reference works that Lao-zi was a mystic. Lao-zi is the reputed founder of religious Taoism and the author of the Dao-de jing. Especially this book is sometimes used to illustrate what is thought to be Taoist mysticism. The cryptic phrase „the valley spirit never dies" (Dao-de jing chap. 6) seems to support such an understanding. On the basis of two essays by the Taoist priest Bai Yu-chan (fl. 13th ct.) which partly discuss that sentence, fundamental elements of the Taoist theory are presented. Special reference is made to the culture of the Taoist priest (dao-shi) and the spiritual basis for this profession. According to Taoist sources there is a unique relationship to the body deities and to the sphere of the divine at all. The spheres of the divine and the human body overlap. Anybody who wants to live up to the genuine divine nature of human life has to handle properly the Taoist mysteries which stand for the very essence of human life. A literary documentation ( Yixian zhuan) and references to historic representatives of professional Taoism (Wei Hua-cun/Shang-qing Taoism; Zhang Yu-chu/Zheng-yi Taoism) give evidence. The conclusion is that Taoist religion is not a mystical religion, although it has its specific mysteries. The Taoist conviction focuses on the sovereign man and his/her divine nature. It is desired to realise and to retrieve this divine nature. The practical aspects of religious Taoism and its basic intentions do not make it directly comparable to indoeuropean approaches in mysticism.